One medicine approach to emerging zoonotic diseases: a review (2008)
Reportedly first espoused by a Physician Sir William Osier, founder of the medical teaching concept at Johns Hopkins University, in the 1800s who wrote that "Veterinary medicine and human medicine complement each other and should he considered as one medicine”, the term "One Medicine," which seeks to promote a unified medical and veterinary medical strategy against zoonotic diseases, was re-echoed in the 1960s by Hr. Calvin W. Schwabe, the late Veterinary epidemiologist and parasitologist at the University of California, Davis. In the face of recent surge in emerging zoonotic disease outbreaks including the Nipah virus. Severe Acute Respiratory Syndrome (SARS) and Avian Influenza (A) IISNI, that are spreading across Asia, Africa, and Europe; and the attendant danger to human health, the concept is now being re-echoed and promoted worldwide. Variously referred to as "One World, One Medicine", "One World, One Health" or simply "One Health" concept, the "One Medicine" approach, which combines the resources of public health, veterinary medicine (more specifically zoonoses), and environmental epidemiology (epizootiology), has been recognized as the major approach to meeting the challenge of emerging zoonotic diseases- diseases transmitted to humans from animals. This paper reviews the "One Medicine” concept in the face of the urgent necessity to adequately and effectively tackle the scourge of emerging infectious diseases of humans, about 65% of which arc zoonotic. It supports the call for collaborative research between veterinarians and physicians and highlights the mission and vision of the ‘One Health” movement, which is gaining membership worldwide, including Nigeria.